“Ensayo de estabilidad y caracterización de los atributos sensoriales del jugo de limón sutil(Citrus aurantifolia)” - Bravo Lozano, Marilú (2005)
The following is a research which main purpose was to test the stability and the characteristics of the sensory attributes of lemmon juice (Citrus Aurantifolia), because of combined effects in diverse concentrations of sodium benzoate, sugar a different temperature of storage. The procedure was selection and classification of lemmon - washing - disinfecting and rinsing - cutting - the extraction of juice - the addition of sodium benzoate which quantities were (0.01, O.OS, 0.10 and 0.15%), and saccharine (60, 62.5, 65 and 67.5º Brix) - packaging - storing at a temperatura of SºC, 12ºC and ambient temperatura. The result of a biometric analysis of lemmon report was height 46 mm - diamenter 42 mm - weight 45.5 g - peel weight 10.3 g - volume 18 mm. This is a good index to take advantage of this product. In addition to this, used Iemmon juice presents a pH of 2.5 anda percentage of acidity in 5.884 expressed as citric acid anda content of ascorbic acid of 32.625 mg/1 OO. In order to discover the sensory properties of the storaged product, we had a group of panelists carefully selected who were chosen according to their ability, interest, health, time availability and the will to cooperate. Then, they were trained with the product to be tested. After several meetings for discussion with the trained panelist, sensory properties were chosen to evaluate from conserved lemmon juice. For this, The Descriptive Sensory Method was used (QDA) specifically, the profile of taste and to rate it, a non-structured scale was used. The stability of conserved lemmon juice with different quantities of sodium benzoate and saccharine and then storaged in temperatures of SºC, 12ºC and ambient temperature, the one that got the best result of organic qualities of the final product was the sample treated with 0.10% of sodium benzoate and saccharine 65ºBrix. lt was kept under 12ºC of refrigeration temperatura. This sample was the same which didn't report sensory changes during 60 days of storage.